Laser illumination for manipulation of hydrogen charge states in silicon solar cells. Issue 2 (23rd December 2014) - Hamer, Phillip; Wang, Sisi; Hallam, Brett; Wenham, Stuart; Chong, Chee Mun; Wenham, Alison; Abbott, Malcolm
<x xml:space="preserve">Abstract</x> This Letter investigates the important parameters of illumination for control of hydrogen charge states in p‐type silicon solar cells. Through variations in the wavelength and intensity of illumination, evidence is provided for the importance of the neutral charge state of interstitial hydrogen, H0, for the passivation of defects in upgraded metallurgical grade (UMG) silicon. It is shown that through this approach minority carrier lifetimes may be achieved in excess of those realised through previous techniques, resulting in open‐circuit voltages (iVOC) over 710 mV. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)